1990
DOI: 10.1159/000185973
|View full text |Cite
|
Sign up to set email alerts
|

Phenylacetylglutamine and Hippuric Acid in Uremic and Healthy Subjects

Abstract: Phenylacetyglutamine (PAG) and hippuric acid (HA) were determined in protein-free filtrates of plasma and urine from patients with chronic renal failure and healthy subjects, using reverse phase high performance liquid chromatography. Plasma accumulation of the metabolites was detected when the creatinine clearance was below 15 ml/min. Protein-binding studies showed that PAG was not bound to plasma proteins but that HA was partly bound. Concentrations of PAG and free HA in plasma did not correlate with values … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
23
1

Year Published

1996
1996
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 12 publications
2
23
1
Order By: Relevance
“…The low dialysate concentration, low dialytic clearance, and decline in plasma concentration suggest that glycine conversion to hippuric acid may partially account for its reduction in plasma concentrations. Zimmerman et al 34 previously reported that phenylacetylglutamine and hippuric acid had dialytic clearances similar to urea and creatinine. The dialytic clearances and subsequent decline in plasma concentrations of glutamine and glycine may decrease ongoing production of phenylacetylglutamine and hippuric acid, respectively.…”
Section: Discussionmentioning
confidence: 91%
“…The low dialysate concentration, low dialytic clearance, and decline in plasma concentration suggest that glycine conversion to hippuric acid may partially account for its reduction in plasma concentrations. Zimmerman et al 34 previously reported that phenylacetylglutamine and hippuric acid had dialytic clearances similar to urea and creatinine. The dialytic clearances and subsequent decline in plasma concentrations of glutamine and glycine may decrease ongoing production of phenylacetylglutamine and hippuric acid, respectively.…”
Section: Discussionmentioning
confidence: 91%
“…Microbes metabolize phenylalanine to phenylacetic acid, which undergoes glutamine conjugation to form phenylacetylglutamine. Only ∼20% of phenylacetylglutamine is protein bound [40], thus, like TMAO it is dialyzable.…”
Section: Breakdown Of the Gut-epithelial Barrier And Systemic Translomentioning
confidence: 99%
“…17 Although p-cresyl sulfate and indoxyl sulfate are considered representatives of the group of protein-bound solutes caused by high protein binding, 18 PAG is much less protein bound, with a bound fraction of approximately 20%. 16,19 In general, it is often stated that protein binding limits solute removal by the native kidney as well as RRT, thus promoting accumulation and possibly, toxicity. 20 However, it can be assumed that only the free fraction of these solutes is biologically active and potentially harmful to the human body.…”
mentioning
confidence: 99%